2018
DOI: 10.3390/toxins10030104
|View full text |Cite
|
Sign up to set email alerts
|

Biosynthesis and Characterization of Zearalenone-14-Sulfate, Zearalenone-14-Glucoside and Zearalenone-16-Glucoside Using Common Fungal Strains

Abstract: Zearalenone (ZEN) and its phase II sulfate and glucoside metabolites have been detected in food and feed commodities. After consumption, the conjugates can be hydrolyzed by the human intestinal microbiota leading to liberation of ZEN that implies an underestimation of the true ZEN exposure. To include ZEN conjugates in routine analysis, reliable standards are needed, which are currently not available. Thus, the aim of the present study was to develop a facilitated biosynthesis of ZEN-14-sulfate, ZEN-14-glucosi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
34
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 33 publications
(36 citation statements)
references
References 26 publications
1
34
0
1
Order By: Relevance
“…Mycotoxin-free whole-wheat grains were bought at a local supermarket (BIO Weizen) and milled to grain flour (ring sieve pore size: 0.5 mm) using an Ultra-Centrifugal mill ZM200 (Retsch, Haan, Germany). Artificially contaminated wheat flour was obtained as previously described by Borzekowski et al (2018) for the inoculation of rice. In brief, moistened wheat grain flour was autoclaved and inoculated with Fusarium graminearum (strain F1 as described by Dubos et al 2011) and incubated for 21 days.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Mycotoxin-free whole-wheat grains were bought at a local supermarket (BIO Weizen) and milled to grain flour (ring sieve pore size: 0.5 mm) using an Ultra-Centrifugal mill ZM200 (Retsch, Haan, Germany). Artificially contaminated wheat flour was obtained as previously described by Borzekowski et al (2018) for the inoculation of rice. In brief, moistened wheat grain flour was autoclaved and inoculated with Fusarium graminearum (strain F1 as described by Dubos et al 2011) and incubated for 21 days.…”
Section: Methodsmentioning
confidence: 99%
“…Subsequently, the flour was autoclaved to terminate the incubation, freeze dried and milled again for homogenisation. The resulting toxin-rich flour contained 541.4 mg/kg ZEN, 3.0 mg/kg α-ZEL, 11.4 mg/kg β-ZEL, 6.4 mg/kg ZAN and 3.4 mg/kg β-ZAL respectively (Borzekowski et al 2018). Additionally, a wheat lot naturally contaminated with ZEN was provided by the European Reference Laboratory for mycotoxins (Geel, Belgium).…”
Section: Methodsmentioning
confidence: 99%
“…Zearalenone was purchased from SantaCruz Biotechnology Inc. (Santa Cruz, CA, USA) with a purity of 99%. Zearalenone-14-sulfate was produced by a double-staged biosynthesis and preparative fractionation as previously described [ 48 ]. α-zearalenol (α-ZEL), β-ZEL and dimethyl sulfoxide were purchased from Sigma-Aldrich Chemie GmbH (Steinheim, Germany).…”
Section: Methodsmentioning
confidence: 99%
“…It might be happened since DON reduction by A. oryzae KKB4, and R. oryzae KP1R1 was enzymatic and resulting in the changing of DON structure (data not shown), such as disrupting the double bond in the A-ring at C9, disrupting the R5 keto functional group at C8 and modification at C3 (Foroud et al, 2016). Studies by Borzekowski et al (2018) showed that genera Aspergillus and Rhizopus can reduce the toxicity by glycosylation at C3 in trichothecenes.…”
Section: Don Detoxification By a Oryzae Kkb4 And R Oryzae Kp1r1mentioning
confidence: 99%